(untitled) (Annual of the Faculty of Philosophy in Skopje, 2020)
The constant claim, even in the 21st century, that Macedonians are a nation invented by the Comintern and Tito’s Yugoslavia requires research to show that the formation of the Macedonian nation was not at all a solution of an international leftist organisation, but a natural process, similar as with other nations in the region. The proximity of the Macedonian with the Bulgarian language, and partly with the Serbian language, is not at all an argument for denying the existence of the Macedonian language as a separate South Slavic language. At the end of the 19th and the beginning of the 20th century, the struggle led by the Macedonian Revolutionary Organisation for the creation of an autonomous Macedonian state aroused great interest among diplomats, politicians, journalists and intellectuals in Europe and the United States. As a result of that interest, many studies and pamphlets related to Macedonia and the possible solution of the Macedonian issue emerged. While seemingly the theses of the sciences from some neighbouring countries are in their favour, careful researches show something quite opposite. Namely, many perceived that the Macedonian Slavic population was neither Bulgarian nor Serbian, but separate South Slavic people appropriated by the neighbours. Moreover, in the United States, for example, where there was a right to free expression of national feeling, some Macedonian emigrants declared themselves as they felt, that is, as Macedonians.